Tingkat Pengungkapan Informasi Website Sebagai Pemoderasi Volume Perdagangan dan Kapitalisasi Pasar Terhadap Return Saham - Pramesti, Hanifah Zulia; Prastyatini, Sri Lestari Yuli (Universitas Hamzanwadi, 2025)
The purpose of this study is to determine how much trading volume (X1) and market capitalization (X2) affect stock returns (Y) with the level of website information disclosure (Z) as a moderation variable. The method used is quantitative and the data is obtained in the form of secondary data. This object uses LQ45 indexed companies with a sample of 100 data from 20 companies for 5 (five) years, namely 2019 to 2023 through a purposive sampling technique. The findings from the hypothesis test indicate positively and significantly that trading volume and market capitalization have an influence on stock returns. The level of website information disclosure is able to moderate well market capitalization and stock returns. But on the other hand, it is unable to moderate the relationship of trading volume to stock returns